Disentangling heterogeneity and commonalities in nanotidal Mediterranean lagoons through environmental features and macrozoobenthic assemblages. (31st May 2020) - Gravina, M.F.; Cabiddu, S.; Como, S.; Floris, A.; Padedda, B.M.; Pusceddu, A.; Magni, P.
Abstract: A comprehensive set of physiographic and environmental features, anthropogenic pressures, as well as the soft-bottom macrozoobenthic assemblages were analyzed in seven nanotidal lagoons located in the Sardinia island (western Mediterranean Sea). We hypothesized that the common typology, and the restricted climatic and geographical settings of the studied lagoons could be reflected in a limited environmental and biological heterogeneity, leading to homogeneous or consistent patterns of ecological variability. To test our hypothesis, we (i) evaluated the extent of environmental heterogeneity of the lagoons under scrutiny to single out the main features accounting for most of the variation among them, and (ii) analyzed the within- and among-lagoons' variation in macrozoobenthic assemblages to identify common patterns and/or a pool of recurrent species, peculiar to distinctive zones within individual lagoons. In terms of physiographic/environmental features, freshwater inputs, minimum salinity and chlorophyll- a were the best explanatory variables arranging the lagoons in three distinct clusters. The environmental integrative index (EII), based on the anthropogenic pressures, further allowed a significant separation of the lagoons, with Santa Gilla and Casaraccio being the most and the least impacted ones, respectively. In all of the investigated lagoons, the distribution of dominant macrozoobenthic species was mainly related to the land-sea gradient, the degree of confinement and the organic enrichment of sediments. Accordingly, we identified four major pools of most distinctive species (60 out of a total of 211 species/taxa found), including (i) opportunistic species, (ii) brackish/halolimnobic species, (iii) species typical of coastal sheltered waters, and (iv) properly marine species. We also identified differences in the macrozoobenthic community composition among lagoons, mostly attributable to the origin of the assemblages, and the dispersal ability and colonization adaptability of individual species. Our results show that single benthic macroinvertebrate species are useful indicators for characterizing the within-lagoon heterogeneity, whereas the assemblage's composition best highlights differences among lagoons. We, thus, raise the need for a thorough analysis of the benthic biodiversity, including the species-specific life history and autecology of the dominant species, to enhance our comprehension of local spatial patterns and the connectivity between lagoons. Overall, the present study demonstrates the usefulness of our approach to disentangle heterogeneity vs. commonalities within and among nanotidal lagoons. Highlights: Environmental features and macrobenthic assemblages investigated in seven Mediterranean lagoons. Within-lagoon common patterns related to salinity, confinement and organic enrichment. Among-lagoon differences determined by individual species. Species' autecology helps explaining local spatial patterns and connectivity among lagoons. Our approach sheds light on heterogeneity and commonalities within and among lagoons.